Status and Conservation Possibilities of Papua New Guinea’s Terrestrial Mammals - David Lopez Cornelio (Institut Pertanian Bogor (IPB University), 2011)
The status of Papua New Guinea’s terrestrial mammals is revised according to their geographical distribution, life history characteristics, and current conservation plans and legislation. Considering their uniqueness and threatening factors, their appropriate management is critical to achieve sustainable development in the country. Concerning marsupial species no one has been yet domesticated, there is no organized breeding and their natural productivity is generally lower than ruminants. Their conservation status is related to their size as smaller species are usually more prolific, less conspicuous, and less preferred by hunters. Differences on evolutionary ecology between families are discussed, and recommendations are given for the assessment and further conservation of vulnerable species. Conservation programs must go alongside with rural livelihoods improvement through ecotourism, food security, and marketing of non timber forest products.